Exploring critical reading of poetry in utar undergraduate students: An eye-tracking case study - Chin, Chun Yuan (2025)
Critical reading is an important skill and is regarded as crucial in this era of globalisation. It is defined as the ability to analyse, interpret, and evaluate the contents of any written text. However, critical reading levels in Malaysian schools have been unsatisfactory. This paper aims to discover the challenges faced when applying critical reading in poetry. By examining a sample of EDEL students in how they read and analyse poems, this research aims to discover the effect of critical reading on students’ poetry comprehension. Using purposive sampling, 7 Year 3 students from the FAS faculty of UiTM were chosen to read two Malaysian English poems while their visual patterns were tracked using eye-tracking equipment before a semi-structured interview that tested their comprehension and their knowledge of critical reading. The eye-tracking results were analysed using a set of five pre-determined reading categories, while the interview transcripts were set to undergo thematic analysis. The research’s results indicated that the visual patterns of the respondents whilst they read the poems were affected by a combination of objective, length and arrangement of poems as well as the complexity of language in the poem. The researcher also discovered that language proficiency and poetic devices were the main challenges the readers faced when critically analysing poems. At the end of the paper, the research notes down several limitations encountered in this experiment’s design as well as a few recommendations when reimplementing this research in future studies.